A cross-sectional Study on lifestyle factors influencing gastritis and dyspepsia among international students’ faculty of medical university - Zoya Petrovna, Lemeshevskaya; Liyanage, L. R. Sathisha Deshan; Rajendrakumar Patel, Grishma; Rilwan Maryam, Mohamed (International Journal of Research in Medical Sciences, 2024)
Background: Gastritis is the syndrome associated with the inflammation of the stomach epithelium. Age, dietary pattern, health issues, level of stress, the existence of any other gastrointestinal symptoms, smoking, use of alcohol, and use of over-the-counter medication were considered extraneous variables. The purpose of this study was to determine the lifestyle characteristics that predispose to gastritis among the international students of Grodno State Medical University, Belarus and the results were closely and meticulously analyzed. Methods: A descriptive survey strategy was used to evaluate the variables associated with gastritis. A simple random approach was chosen for this research. Data was collected with the help of a questionnaire in the format of an online Google form and recorded. Responses from 211 respondents mostly aged 18 to 29 years old were collected. The survey focused on gastritis and its connection to lifestyle factors like smoking, stress, and eating patterns. Results: The frequency value for the consumption of processed food was the highest above all with regards to dietary habits in this study followed by consumption of fibrous food, having carbonated drinks, frequency of having coffee/tea per day, and general stress level with their daily workload as well as evidently due to consumption of spicy food. Conclusions: This study demonstrates that the incidence of gastritis among the respondents was multifactorial.